(untitled) (Archives of Criminology, 2008)
The text presents the formation of criminology as a new science in Russia from the 19th to the 20th century. The study is the outcome of the author’s interest in criminological research on the problem of organised crime and criminal law in Russia. The analysis presented in the article deals with the most important events in Russian politics that influenced the development of criminological studies. Among them, the author mentions the meetings of the Russian Academy of Sciences in 1823 and thus the gradual development of specialisations in sociology and anthropology, the October Revolution and the establishment of the Petrograd Criminological Cabinet in 1917, or the founding of the State Institute for the Study of Crime and the Criminal in 1925. The text also highlights the problem of the widespread belief in the non-existence of social causes of crime – considered a hallmark of capitalism – and thus the waning interest in crime research in the early days of the USSR. Katarzyna Laskowska then analyses the revival of criminology in the 1960s after Stalin’s death and the creation of the All-Union Institute for the Study of the Causes of Crime and the Development of Ways to Counteract Crime in 1963, as well as the publication of its first textbook on criminology. The text further describes the development of criminology in the 1980s and 1990s under the conditions of social non-publicity in Russia. Finally, the author provides an outlook on the development of criminology in Russia since the 1990s, stressing that political, social, and economic changes have had a considerable impact on the development of this science. The text emphasises that current Russian criminologists are active and that their research contains valuable insights. According to Laskowska, the future of the science is in no way threatened in Russia by changes in crime.